Kempinski Hotels - Neck, Christopher P., (SAGE Knowledge. Cases., 2017)
Kempinski Hotels, headquartered in Switzerland, is Europe's oldest luxury hotel group, specializing in five-star properties that include the Emirate's Palace in Abu Dhabi, the Hotel Taschenbergpalais Kempinski in Dresden, and the C'iragan Palace Kempinski in Istanbul. Founded in 1897, the Kempinski brand has an intriguing story to tell. "Our employees have been a part of creating history around the world," the website reads. "From historic buildings to the most avant-garde of modern architecture, our properties are the setting for some of lifes greatest moments. We've witnessed historic meetings between world leaders, celebrities taking sanctuary in the world of calm we create for them, and created incredible memories for guests on a once-in-a-lifetime journey."